2022
DOI: 10.3390/foods11010109
|View full text |Cite
|
Sign up to set email alerts
|

Bioproduction of 2-Phenylethanol through Yeast Fermentation on Synthetic Media and on Agro-Industrial Waste and By-Products: A Review

Abstract: Due to its pleasant rosy scent, the aromatic alcohol 2-phenylethanol (2-PE) has a huge market demand. Since this valuable compound is used in food, cosmetics and pharmaceuticals, consumers and safety regulations tend to prefer natural methods for its production rather than the synthetic ones. Natural 2-PE can be either produced through the extraction of essential oils from various flowers, including roses, hyacinths and jasmine, or through biotechnological routes. In fact, the rarity of natural 2-PE in flowers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 83 publications
0
45
0
Order By: Relevance
“…Optimizing the use of waste in the raw state (undiluted), to produce value-added metabolites, has operational and economic advantages. At an operational level, it allows lower operating volumes and, as observed in this study, it contributes to the remediation of sweet whey, with which a significant economic benefit could be obtained [6].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Optimizing the use of waste in the raw state (undiluted), to produce value-added metabolites, has operational and economic advantages. At an operational level, it allows lower operating volumes and, as observed in this study, it contributes to the remediation of sweet whey, with which a significant economic benefit could be obtained [6].…”
Section: Discussionmentioning
confidence: 68%
“…As pointed out in the introduction, few studies explore the use of industrial waste to produce aromatic compounds, especially using them crude, that is, undiluted. The review carried out by [6] presents an analysis of the investigations that have used agro-industrial residues. Like the grape must, where the production of 2-PhEtOH was 0.39 g/L with 3 g/L of precursor in 84 h of culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol is typically derived from glucose metabolism and fermentation, while 1-butanol, 3-methyl- is produced from the downstream breakdown of leucine [ 25 ]. 2-phenylethyl alcohol is produced from the degradation of aromatic amino acids [ 6 ] via the shikimate pathway [ 26 ]. These core alcohols that both Candida species emitted are not characteristic and are common metabolic products that are widely emitted across both bacterial and fungal kingdoms [ 6 , 11 , 22 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, microbial fermentation is a promising biovalorization method for this highvolume industrial byproduct [2]. For instance, it was reported that this cheap feedstock was used to naturally produce the valuable aromatic compound 2-phenylethanol through microbial fermentation mainly using yeasts, competing with the conventional, environmentally unfriendly, chemical synthesis routes [15]. A simplified scheme of the brewing process, BSG constituents, and their uses, is illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%